Fatigue and its associated risk factors among shift workers: A systematic review. - M. S., Abu Hanifah; Norazura, Ismail (Wiley, 2020)
Shift workers in various occupations are at risk of getting fatigued due to the nature of their work. This study provides a systematic outline of the occurrence of fatigue and its risk factors for shift workers in various industries worldwide within the decade. A systematic review from five literature databases was searched using three keywords, namely fatigue, shift work, and shift workers. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines were used, and two reviewers reviewed the titles separately, picked abstracts, full texts, and checked their quality based on the predefined criteria. The search strategy for initial literature resulted in 3829 potential articles, but only 29 articles were included in this review. Differences in the definition of fatigue and the assessment method used were found to have resulted in the different prevalence of fatigue from various studied occupations. Eighteen risk factors divided into sociodemographic, work‐ related, and outside of work factors were found. This review demonstrates that fatigue is a significant issue for shift workers with various risk factors involved. Future research in regard to the epidemiology of fatigue should focus on related risk factors. Thus, an appropriate intervention program to reduce fatigue could be developed and executed effectively towards lowering fatigue cases among shift workers.